2013
DOI: 10.5380/ce.v18i1.28977
|View full text |Cite
|
Sign up to set email alerts
|

Implantação De Ações Para Enfrentamento Do Consumo De Drogas Na Atenção Primaria a Saúde

Abstract: RESUMO:O estudo avaliou a implantação de diretrizes para atenção integral a usuários de álcool e outras drogas na Atenção Primária à Saúde, por meio de pesquisa avaliativa de estudo de caso, utilizando-se a diretriz do Ministério da Saúde para esta política pública. Participaram gestores municipais e profissionais de saúde de uma Unidade Básica de Saúde, sendo a maioria mulheres com idade entre 30 e 49 anos e tempo no cargo/função inferior a cinco anos. Como julgamento preconizou-se que a proporção de resposta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
2
0
5
Order By: Relevance
“…Alegase, ainda, a falta de comunicação entre Estratégia de Saúde da Família e o CAPSad de referência. Diante dos achados, os autores concluem sobre a necessidade de aperfeiçoamento da atenção à Saúde Mental e para a importância da análise do papel dos diferentes equipamentos de saúde que compõem a rede de saúde, ponderando que a atenção integral é constituída por um conjunto de dispositivos intersetoriais (15) .…”
Section: Discussionunclassified
“…Alegase, ainda, a falta de comunicação entre Estratégia de Saúde da Família e o CAPSad de referência. Diante dos achados, os autores concluem sobre a necessidade de aperfeiçoamento da atenção à Saúde Mental e para a importância da análise do papel dos diferentes equipamentos de saúde que compõem a rede de saúde, ponderando que a atenção integral é constituída por um conjunto de dispositivos intersetoriais (15) .…”
Section: Discussionunclassified
“…de prevenção e atuação mais democrática na área da saúde. Além de propiciar, o engajamento da comunidade, por meio de suas associações, organizações, redes de interação social, grupos e organizações religiosas, na discussão da problemática do uso de drogas OLIVEIRA, 2013;BRASIL, 2005).…”
Section: Categoria 3: Percepções Sobre a Redução De Danosunclassified
“…42 , which, despite being considered a milestone to guarantee the protection of children's and adolescents' rights -seeking to ensure the citizenship of these subjects -does not clearly state how care should be provided to this public in health institutions. In this same document, article 101, dealing with the Specific Protection Measures, establishes that child or adolescent drug users should "receive temporary guidance, support and follow-up; request for medical, psychological or psychiatric treatment in a hospital or outpatient setting or inclusion in an official or community program of care, guidance or treatment for alcoholics and drug addicts" 43,44 . In this regard, Vilarins 45 agrees with the idea that the ECA only signals to the fact that adolescents with drug abuse-related problems will receive individual and specialized treatment, in a place appropriate to their conditions, but does not point the locations for this kind of care and the guidelines for the treatment.…”
Section: Meanings Attributed To Institutional Reception: From Institumentioning
confidence: 99%
“…Thus, although CAPSi focuses on severe and persistent mental disorders 44 , it is well known in practice that this service also provides care to adolescent drug abusers of up to 15 years of age. However, the service did show some constraints with regard to working with this public, since in situ observations revealed that only one professional was responsible for the care of this population.…”
Section: Leadership Of the Institutional Reception And Psychosocial Cmentioning
confidence: 99%